Optimized methods for preparation of 6I-(ω-sulfanyl-alkylene-sulfanyl)-β-cyclodextrin derivatives - Bednářová, Eva; Hybelbauerová, Simona; Jindřich, Jindřich (Beilstein Journal of Organic Chemistry, 2016)
A general high-yielding method for the preparation of monosubstituted β-cyclodextrin derivatives which have attached a thiol group in position 6 is described. The thiol group is attached through linkers of different lengths and repeating units (ethylene glycol or methylene). The target compounds were characterized by IR, MS and NMR spectra. A simple method for their complete conversion to the corresponding disulfides as well as a method for the reduction of the disulfides back to the thiols is presented. Both, thiols and disulfides are derivatives usable for well-defined covalent attachment of cyclodextrin to gold or polydopamine-coated solid surfaces.
Keywords: cyclodextrins; disulfides; monosubstituted derivatives; thiols

(untitled) - Crini, G. (Chem. Rev., 2014)

(untitled) - Rekharsky, M. V.; Inoue, Y. (Chem. Rev., 1998)

Modified Cyclodextrins: Scaffolds and Templates for Supramolecular Chemistry - Easton, C. J.; Lincoln, S. F. (Imperial College Press, 1999)

(untitled) - Hedges, A. R. (Chem. Rev., 1998)

(untitled) - Tang, W.; Ng, S. C. (J. Sep. Sci., 2008)

(untitled) - Han, C.; Li, H. (Anal. Bioanal. Chem., 2009)

(untitled) - Wang, L.; Li, L.-l.; Fan, Y.-s.; Wang, H. (Adv. Mater., 2013)

(untitled) - Crini, G.; Morcellet, M. (J. Sep. Sci., 2002)

(untitled) - Ulman, A. (Chem. Rev., 1996)

(untitled) - Vericat, C.; Vela, M. E.; Benitez, G. A.; Gago, J. A. M.; Torrelles, X.; Salvarezza, R. C. (J. Phys.: Condens. Matter, 2006)

(untitled) - Lee, H.; Dellatore, S. M.; Miller, W. M.; Messersmith, P. B. (Science, 2007)

(untitled) - Rojas, M. T.; Königer, R.; Stoddart, J. F.; Kaifer, A. E. (J. Am. Chem. Soc., 1995)

(untitled) - Henke, C.; Steinem, C.; Janshoff, A.; Steffan, G.; Luftmann, H.; Sieber, M.; Galla, H.-J. (Anal. Chem., 1996)

(untitled) - Kikandi, S. N.; Okello, V. A.; Wang, Q.; Sadik, O. A.; Varner, K. E.; Burns, S. A. (Environ. Sci. Technol., 2011)

(untitled) - Yang, H.; Lan, Y.; Zhu, W.; Li, W.; Xu, D.; Cui, J.; Shen, D.; Li, G. (J. Mater. Chem., 2012)

(untitled) - Nelles, G.; Weisser, M.; Back, R.; Wohlfart, P.; Wenz, G.; Mittler-Neher, S. (J. Am. Chem. Soc., 1996)

(untitled) - Popr, M.; Hybelbauerová, S.; Jindřich, J. (Beilstein J. Org. Chem., 2014)

(untitled) - Zhong, N.; Byun, H.-S.; Bittman, R. (Tetrahedron Lett., 1998)

(untitled) - Bonger, K. M.; van den Berg, R. J. B. H. N.; Heitman, L. H.; IJzerman, A. P.; Oosterom, J.; Timmers, C. M.; Overkleeft, H. S.; van der Marel, G. A. (Bioorg. Med. Chem., 2007)

(untitled) - Scullion, L. E.; Leary, E.; Higgins, S. J.; Nichols, R. J. (J. Phys.: Condens. Matter, 2012)

(untitled) - Keddie, D. J.; Grande, J. B.; Gonzaga, F.; Brook, M. A.; Dargaville, T. R. (Org. Lett., 2011)

(untitled) - Harada, A.; Okada, M.; Kawaguchi, Y.; Kamachi, M. (Polym. Adv. Technol., 1999)